The effective length estimation of columns in semi-rigid jointed braced frames - Ismail Meghezzi-Larafi; Abdelouahab Tati (Journal of Applied Engineering Science and Technology, 2016)
This paper presents a theoretical and exact procedure for the stability analysis of bracedsteel frames, taking in account the flexibility effect of the beam-column connections. In order todetermine the effective length factor (K-factor). The isolated subassembly approach is used toestablish the buckling governing equation. In this study, the relative stiffness coefficient at theisolated column ends is provided by the remainder members of the structure, rather than of therelative stiffness factor in the alignment chart method. A computer program for plane structureanalysis is used to evaluate the relative stiffness coefficients. To illustrate the accuracy of theestablished transcendental equation, K-factor values for the case of fully rigid connections, arecompared to the exact and the French rules results. The effect of the type of transfer elementsbetween the frame members, in term of fixity factors is investigated. Moreover, the effect ofrestraining conditions, provided by the whole frame structure, in term of relative stiffnesscoefficients, is also studied. The obtained results revealed that the buckling critical loads of thecolumns in frames of rigid members are significantly affected by the fixity factors variation, unlikein flexible structures.